A Rapidly Progressive Variant of Psoriatic Arthritis: Psoriatic Onycho-Pachydermo-Periostitis - Sibel SÜZEN ÖZBAYRAK; Vildan BİNAY SAFER and Mustafa ÖZBAYRAK (Archives of Rheumatology, 2016)
We present a case with psoriatic onychodystrophy, onycholysis, connective tissue thickening above the distal phalanx as well as specific radiologic changes diagnosed as psoriatic onycho-pachydermo-periostitis who responded dramatically to methotrexate with current literature review. In this article, we report a 53-year-old male patient with psoriatic onycho-pachydermo-periostitis who responded dramatically to methotrexate.